Maternal Knowledge on Postpartum Care in Healthcare Centers of Mashhad, Iran in 2013 - Khadijeh Mirzaee; somayyeh oladi ghadikolaee; Mohamad Taghi Shakeri; seyed mojtaba mousavi Bazzaz (Mashhad University of Medical Sciences, 2015)
Background & aim: During the postpartum period, women experience physiological changes, which can have negative impacts on their quality of life. Women's knowledge regarding postpartum complications and care can help them successfully pass this critical period. The aim of this study was to evaluate maternal knowledge on postpartum care in healthcare centers of Mashhad, Iran in 2013. Methods:In this descriptive, cross-sectional study, 500 eligible mothers were randomly selected via multistage sampling from 19 healthcare centers of Mashhad. Data collection tools included a demographic questionnaire and a researcher-made questionnaire for assessing maternal knowledge. Descriptive and analytical statistics, independent t-test, analysis of variance, Pearson's correlation coefficient and multivariable regression analysis were applied, using SPSS version 16. P-value less than 0.05 was considered statistically significant. Results: Among 500 mothers referring to healthcare centers, 64 (12.8%), 396 (79.2%) and 40 (8.0%) cases had poor, moderate and high levels of knowledge, respectively. The majority of mothers had moderate knowledge about four dimensions of public health, breastfeeding and nutrition, contraceptive methods and infant care. The subjects had the highest and lowest levels of knowledge about public health and contraceptive methods, respectively. The results showed a significant relationship between the mean score of knowledge and demographic characteristics such as educational status, employment status and income level (P